Spectrophotometric Simultaneous Kinetic Determination of Iodide and Iodate Using Partial Least-Squares Calibration Method in a Single Kinetic Run (Journal of Sciences, Islamic Republic of Iran)
A rapid, sensitive and versatile kinetic method is presented for the simultaneous spectrophotometric determination of iodide and iodate by partial least-squares regression (PLS) using original and derivate data named as absorbance and rate data. The method is based on the catalytic effect of the cited anions on the reaction rate between Ce(IV) and As(III) in 2 mol l?1 sulfuric acid medium. The Savitzky-Golay convolution method is used for calculating and smoothing the rate data. Results show that PLS is an excellent calibration method to resolve the mixtures of two anions by first-order or pseudo first-order kinetic procedures without any previous knowledge about rate constant values. The 26 calibration solutions were made of iodide and iodate in the range of 10-48 and 55-235 ng ml?1. The RMSEP calculated for 12 test solutions are 0.1756, 0.5074 and 0.2327, 0.9197 for the absorbance and rate data for iodide and iodate respectively. The application of the method was confirmed by analysis of these anions in real matrix samples.